Gendered Citation Patterns in International Relations Journals1. Issue 4 (27th June 2013) - Mitchell, Sara McLaughlin; Lange, Samantha; Brus, Holly
Abstract : This paper applies a methodology utilized in economics to study citation patterns in two International Studies Association journals. The paper analyzes articles published in International Studies Quarterly (ISQ) and International Studies Perspectives (ISP) in 2005. Comparisons are made based on the sex of the authors of articles and the sex of the cited authors in each paper's bibliography. Empirical analyses suggest that male authors of ISQ and ISP articles are less likely to cite work by female scholars in comparison with female authors. Mixed‐gender author teams are also significantly less likely to cite research by female scholars relative to female article authors.